2014
DOI: 10.1242/jcs.143677
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a regulates zebrafish myogenesis via targeting the transcription factor Six1

Abstract: Precise spatiotemporal regulation of the SIX1 homeoprotein is required to coordinate vital tissue development, including myogenesis. Whereas SIX1 is downregulated in most tissues following embryogenesis, it is re-expressed in numerous cancers, including tumors derived from muscle progenitors. Despite crucial roles in development and disease, the upstream regulation of SIX1 expression has remained elusive. Here, we identify the first direct mechanism for Six1 regulation in embryogenesis, through microRNA30a (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 81 publications
2
23
0
Order By: Relevance
“…Recently, a strong selective sweep near the vgll3 gene was postulated to be due to energy metabolism effects in humans in Mongolia (Nakayama et al 2017). In turn, genes in the six6 genomic region are involved in cell growth, cell differentiation, apoptosis in human cell lines ( PPM1A , Lin et al 2006), and myogenesis and skeletal muscle cell proliferation in zebrafish ( six1b , Ridgeway and Skerjanc 2001, Bessarab et al 2004, O’Brien et al 2014) and act as an evolutionarily conserved regulator of eye development and the pituitary–hypothalamic axis ( six6 , Serikaku and Otousa 1994, Toy et al 1998, Gallardo et al 1999). Collectively, this suggests that the vgll3 and six6 haploblocks might have broad-scale roles in reproductive and life-history strategies in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a strong selective sweep near the vgll3 gene was postulated to be due to energy metabolism effects in humans in Mongolia (Nakayama et al 2017). In turn, genes in the six6 genomic region are involved in cell growth, cell differentiation, apoptosis in human cell lines ( PPM1A , Lin et al 2006), and myogenesis and skeletal muscle cell proliferation in zebrafish ( six1b , Ridgeway and Skerjanc 2001, Bessarab et al 2004, O’Brien et al 2014) and act as an evolutionarily conserved regulator of eye development and the pituitary–hypothalamic axis ( six6 , Serikaku and Otousa 1994, Toy et al 1998, Gallardo et al 1999). Collectively, this suggests that the vgll3 and six6 haploblocks might have broad-scale roles in reproductive and life-history strategies in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, the Six1a ortholog drives proliferation and differentiation of zebrafish embryonic muscle fiber precursor cells, and its knockdown results in apoptosis (O'Brien et al, 2014). Six1 also plays a key role in the transcriptional regulation of the myogenic regulatory factor (MRF) gene family (Fougerousse et al, 2002; Grifone et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There are MEF3 sites in the core area of the MyoG enhancer, and when Six1 combines with MEF3, MyoG is expressed (Zhang et al, 2009). In zebrafish, more than half of the embryos were MyoG negative cells when Six1a expression was blocked, and the process of rapid muscle differentiation was inhibited (O'Brien et al, 2014). Previous studies have suggested that over expression of Six1 up-regulates MyoG expression and over expression of Six4 down-regulates MyoG expression (Yajima et al, 2010).…”
Section: Discussionmentioning
confidence: 99%